A Prioritization Approach for Noise Risk Management in a Petrochemical Complex. Issue 3 (4th October 2013) - Nassiri, Parvin; Dehghan, Somayeh Farhang; Monazzam, Mohammad Reza
Abstract : A Prioritization Approach for Noise Risk Management in a Petrochemical Complex: Parvin NASSIRI, et al . Department of Occupational Health, School of Public Health, Tehran University of Medical Sciences, Iran— Objectives: Noise is probably the most common occupational hazard facing workers today. This paper presents a model to evaluate and select a unit as the first priority for implementing noise control measures from the different parts of an industrial complex. Methods: For this purpose, a formula was proposed as a priority risk index (NCPI) by considering some criteria, including: the number of exposed workers in each part, their exposure times and the range of sound pressure level. The above criteria were weighed by appending weighting factors, which can be different based upon the environmental noise levels. The environmental noise measurements were also carried out by lattice method according to ISO 9612:2009. At the next stage, the numbers of stations that fell within the desired ranges in the weighting factors table were found. Then the priorities were identified using the above criteria and the NCPI. Results: The results indicate that the compression unit of air plant had the highest score among the different departments of the company under study (NCPI=0.3). Using this model is easy and fast. It is applicable to similar industries and also offers valuable information for prioritizing noise control measures. Conclusions: Therefore, it will be possible to minimize worker exposure to noise in the most polluted places in any industry by identifying the main noise sources and implementing measures suitable for controlling the risk.